O Berrão de Ramilo, Duas Igrejas, Miranda do Douro: Nota preliminar - Salgado, Mónica; Queiroga, Francisco M.V. Reimão (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2021)
The statue of wild boar from Ramilo, now presented, was recently discovered in the course of agricultural work within the boundaries of the Duas Igrejas parish, Miranda do Douro Council, in a property named Ramilo. This is an important find amongst the existing statues of the kind, as it represents a male wild boar depicted with a number of sculpted details that altogether add to the definition of the typologies of representation of the boar statues so far found in this region.